WEBB, H.S. Inventory of documents - WEBB, H.S. (ARCA, 2018)
Born on 26 February 1883 at Grahamstad, Founder member of Waakzaamheidskomite in 1912 – predecessor of the National Party; cartoons; scrapbook on trial of Genl CR de Wet; photos
COVERAGE: 1915; 0.01 metres
Keywords: WEBB, H.S.; Inventories; Politicians; National Party; Waakzaamheidskomite